The Impact of University Uniqueness on Indonesian Universities' Competitiveness in the New Normal Education System - Bob Foster; Muhamad Deni Johansyah (AL-ISHLAH: Jurnal Pendidikan, 2021)
The new normal learning process remains extremely difficult to implement due to changing one's mentality. Educators are not agents of knowledge dissemination. Nonetheless, it must fundamentally transform into motivators, inspirations, and collaborators in the process of developing the capacity to ask critical questions about the information contained in cyberspace and the general dearth of universities. It can organize online higher education programs properly is still a small number and coupled with students' lack of comprehension of the material provided by the lecturer online, which is significantly different from the face-to-face learning method. This research was conducted descriptively by employing a quantitative approach. This research aims to ascertain the capabilities of universities and their impact on the results achieved by universities in terms of competitiveness. The study's findings indicate that the university's unique capability significantly impacts its competitiveness.